Eisenmenger Syndrome and Pregnancy: Novel ECMO Configuration as a Bridge to Delivery and Recovery Utilizing a Multidisciplinary Team. Issue 1 (January 2018) - Rosenzweig, Erika B.; Abrams, Darryl; Biscotti, Mauer; Kerstein, Diane; Drassinower, Daphnie; Brodie, Daniel; Bacchetta, Matthew
Abstract : Pregnancy is typically contraindicated in Eisenmenger syndrome because of its association with excessively high maternal and fetal morbidity and mortality. Here, we report on our novel approach to successfully managing a 29 year old pregnant woman with an unrepaired patent ductus arteriosus (PDA) with Eisenmenger syndrome through delivery and recovery. Venovenous extracorporeal membrane oxygenation (ECMO) was utilized during induction of labor to stabilize maternal hemodynamics and optimize fetal oxygenation by creating an oxygenated right-to-left shunt through the PDA. Delivery ultimately required cesarean section on ECMO support, with her hospital course complicated by intraabdominal hemorrhage and, later, recannulation with venoarterial ECMO for postoperative respiratory failure with decompensated pulmonary hypertension. Ultimately, both the mother and baby were successfully discharged to home. This case highlights not only the potential for ECMO in the peripartum setting for patients with severe pulmonary hypertension, but also the complexity of management and the need for a highly experienced, multidisciplinary team.